An epigenome atlas of mouse adipocytes - Laura C. Hinte; Adhideb Ghosh; Daniel Castellano-Castillo; Christian Wolfrum; Ferdinand von Meyenn (Molecular Metabolism)
Objective: Epigenetic modifications including histone post translational modifications can influence gene expression in adipocytes, potentially contributing to metabolic dysfunctions, obesity, and insulin resistance. Despite recent advances in the characterization of the mouse adipocyte epigenome, epigenetic characterization of adipocytes in vivo has been challenging, particularly across different adipose depots and of several epigenetic modifications. Methods: Here, we use specific reporter mice labelling brown, beige and white adipocytes, diphtheria toxin-mediated ablation of beige adipocytes, and Cleavage Under Targets and Tagmentation (CUT&Tag) to generate paired single mouse datasets of five histone marks. We perform an integrative multi-omics factor analysis (MOFA) of H3K4me3, H3K27me3, H3K4me1, H3K27ac and H3K9me3 in brown, white and beige adipocytes from three distinct mouse adipose tissue depots obtained during cold exposure and thermoneutrality. Results: Our analysis reveals that enhancers distinguish adipocytes by their tissue of origin, with H3K4me1 deposition differentiating between beige and brown adipocytes. Beige adipocytes poised promoters associated to thermogenic genes during warming. Diphtheria toxin-mediated ablation of beige adipocytes shows that non-beigeing white adipocytes in inguinal adipose tissue and beige adipocytes are not inherently epigenetically different suggesting that they share a common developmental progenitor. Conclusions: These paired multimodal data comprise an extensive resource (https://github.com/vonMeyennLab/mAT_CE_Atlas) for the further exploration of the mouse adipocyte epigenome which will enable discovery of regulatory elements governing adipocyte identity and gene regulation.